EFFECT OF LEMON AROMATHERAPY ON DECLINE NAUSEA AND VOMITING IN PREGNANT WOMEN IN THE FIRST TRIMESTER AT THE ABEPURA HEALTH CENTER IN JAYAPURA CITY - Suryati Romauli; Flora Niu (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
Background: Vomiting and nausea in the first trimester of pregnancy is often experienced by pregnant women, if the symptoms occur continuously it will have an impact on pregnancy and the process of fetal growth and development. One of the safe and doable non-pharmacological therapies is the administration of lemon aromatherapy. Objective: This study aims to determine the effect of lemon aromatherapy on reducing nausea and vomiting in pregnant women in the 1 trimester Methods: This type of research is pre-experimental with quasi-experimental design. The design is using two group pretest posttests as a treatment in the intervention group to be given lemon aromatherapy and a control group that was not intervened. The population was 28 pregnant women, with the sample being the total population divided into 2 groups using purposive sampling techniques. Data were obtained using the Pregnancy Unique Quantification of Emesis/Nausea (PUQE) Scale questionnaire to measure the frequency of nausea and vomiting before and after two weeks of aromatherapy. Data analysis using the Wilcoxon Signed Rank Test. Results: The results showed that there was an effect of lemon aromatherapy on reducing nausea and vomiting in 1 trimester pregnant women where statistical tests showed a value Sig (2 tailed)=0,000 < α 0,05 then Ha is accepted. Conclusion: There is an effect of lemon aromatherapy on the decrease in nausea and vomiting in 1 trimester pregnant women